Standards for opioid use disorder care: An assessment of Nordic approaches. Issue 3 (June 2019) - Gedeon, Charlotte; Sandell, Mikael; Birkemose, Inge; Kakko, Johan; Rúnarsdóttir, Valgerður; Simojoki, Kaarlo; Clausen, Thomas; Nyberg, Fred; Littlewood, Richard; Alho, Hannu
Aims: Outcomes in opioid use disorder (OUD) in Nordic countries have improved with integrated treatment and harm-reduction programmes. Approaches and the standard of care are different across the region. Evidence of treatment needs and current approaches are defined from evidence to inform development of a common standard. Method: Evidence of population sizes and treatment approach collected. Common standards for care (harm reduction, pharmacotherapy, psychology/social therapy) defined for each country. Results: Evidence defines number in treatment; potential population needing treatment not defined for all countries. Populations sizes, treatment access (ratio in treatment programme compared to total country population) defined: Sweden 4, 000 in OUD care (access ratio 40); Finland 3, 000 (55); Norway 8, 000 (154); Denmark 7, 500 (132). Approach to treatment similar: integrated treatment programmes standard. Care provided by specialists in outpatient clinics/primary care; secondary care/inpatient services are available. Harm reduction is limited in Sweden but available and more accessible elsewhere. Treatment entry criteria: access relatively unlimited in Norway and Denmark, more limited in Finland and Sweden. Standards of care defined: easy access to high-quality services, individual planning, care not limited by time, management of relapse, education for patients, continuous engagement, holistic approach including management of comorbidities, needle equipment programmes without limit, treatment in prisons as community. Conclusion: There are opportunities to improve OUD care in the Nordics. Policy makers and clinicians can advance OUD care and share common success factors. Collaborative work across the Nordic countries is valuable. Further research in clinical practice development can yield important results for the benefit of patients with OUD.